Análise dos fatores influentes do impacto do treinamento no trabalho: investigação em uma Instituição Federal de Ensino Superior - Cabrera, Rodrigo (Universidade Federal de São Carlos, 2019)
The great importance it has been given to training has led organizations to increasingly evaluate the results of these actions in order to identify how to transfer the knowledge learned in training to the workplace. The effectiveness of training depends on a number of factors, such as the participant's beliefs about training, the motivation to learn, the characteristics of the organization and the support for the transference of learning. These factors can be considered variables that affect the impact of training on the job. In the scenario of the federal public administration, it has been noticed that, due to a growing demand of society for better public services, one of the ways found to improve the management is the training of civil servants. The present study analyzes the impact of work training in a Federal Institution of Higher Education, verifying which are the main factors that influence the process of transferring learning from the trainings to the work routine under the perception of the participants of these trainings. This work also presents the results of a bibliographical research on: the legislations and policies of training of federal public servants, especially those who work for Federal Higher Institutions of Education; the concept and process of personnel training; the main evaluation models found in the literature. Based on current studies, this paper proposes a measurement model of the influential factors in the training impact at work. The statistical technique chosen for the data analysis was the non-parametric structural equations modeling. This is a descriptive, quantitative research, with the application of a web survey. The target public that was studied was a group of technical-administrative civil servants of Federal University of ABC that joined in training from 2014 to 2017. After data collection and analysis, the proposed measurement model was validated and it was identified that the main correlations were perceived between the characteristics of the organization and the psychosocial support offered to the training participants, between the beliefs that the civil servant has got about training and the motivation to learn, and also between the beliefs about training and the impact of training at work. As a final result, the research contributed to the literature by demonstrating the influence that the "beliefs about training" factor has on the impact of training on the job.
Analysis of influent factors of the impact of training at work: research in a Federal Institution of Higher Education
Keywords: Treinamento; Avaliação de treinamento; Impacto do treinamento no trabalho; Training; Training evaluation; Impact of training on the job; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ADMINISTRACAO DE PESSOAL